Analysis of Islamic Education Learning Methods in View of Islamic Educational Philosophy: A Study at Muhammadiyah Junior High School - Susanto, Happy; Sudarmadi , Sudarmadi; Saputro, Anip Dwi; Rois, Adib Khusnul; Munir, Abdul (Universitas Muhammadiyah Sidoarjo, 2024)
Islamic instruction is one of the Islamic ponders that ponders the subject of Islamic instruction. Understanding the nature of Islamic instruction is really contained within the history and logic of Islam itself, since no instructive handle can be isolated from Islamic subjects. Islamic educational reasoning may be a concept that sees instruction based on Islamic lessons and human capacities that must be supported, created and guided in arrange to ended up a Muslim whose whole identity is permeated with Islamic lessons. Philosophical inquire about utilized in Islamic instructive reasoning implies that Islamic instructive logic is profound, efficient, radical and widespread considering that investigates the truth which is the pith of Islamic instruction. The logic of Islamic instruction is based on disclosure and is humanistic, and recognizes boundless and all inclusive truth. The principles and objectives of learning are reviewed from the philosophy of Islamic religious education. Apart from that, there are also many experts who have opinions, especially regarding the definition or understanding of learning methods and also put forward various kinds of learning methods which will be discussed here. Muhammadiyah 4 Balong Ponorogo Middle School has a very good program, namely the Tahfidz al-Quran program, muhadhoroh, and other religious activities. This shows that there are still public schools that still implement Islamic religious education which almost resembles Islamic boarding schools. Researchers are interested in conducting research at SMP Muhammadiyah 4 Balong Ponorogo because looking at the phenomenon above, the cultivation of Islamic religious education by implementing a strong religious formation system is a philosophical value of the philosophy of Islamic education.